Transfer hydrogenation catalysis in cells as a new approach to anticancer drug design - Soldevila-Barreda, Joan J.; Romero-Canelón, Isolda; Habtemariam, Abraha; Sadler, Peter J. (Nature communications, 2015)
Organometallic complexes are effective hydrogenation catalysts for organic reactions. For example, Noyori-type ruthenium complexes catalyse reduction of ketones by transfer of hydride from formate. Here we show that such catalytic reactions can be achieved in cancer cells, offering a new strategy for the design of safe metal-based anticancer drugs. The activity of ruthenium(II) sulfonamido ethyleneamine complexes towards human ovarian cancer cells is enhanced by up to 50 × in the presence of low non-toxic doses of formate. The extent of conversion of coenzyme NAD + to NADH in cells is dependent on formate concentration. This novel reductive stress mechanism of cell death does not involve apoptosis or perturbation of mitochondrial membrane potentials. In contrast, iridium cyclopentadienyl catalysts cause cancer cell death by oxidative stress. Organometallic complexes therefore have an extraordinary ability to modulate the redox status of cancer cells. Organometallic complexes are effective hydrogenation catalysts for organic reactions. Here the authors report for the first time that transfer hydrogenation catalysis can take place inside the cell and could be used as a novel anticancer strategy.